Protective Effects of Aquilaria agallocha and Aquilaria malaccensis Edible Plant Extracts against Lung Cancer, Inflammation, and Oxidative Stress—In Silico and In Vitro Study - Jinnatun Nahar; Vinothini Boopathi; Esrat Jahan Rupa; Muhammad Awais; Anjali Kariyarath Valappil; Md Niaj Morshed; Mohanapriya Murugesan; Reshmi Akter; Dong Uk Yang; Ramya Mathiyalagan; Deok Chun Yang; Seok-Kyu Jung (Applied Sciences, 2023)
The family Thymelaeaceae, which includes huge evergreen trees that are sparsely distributed in tropical rainforests, includes the genus Aquilaria. Numerous medical conditions, including inflammation, cancer, and oxidative stress have been traditionally treated using Aquilaria agallocha and Aquilaria malaccensis. In this study, we evaluated in silico and biological activity with A. agallocha and A. malaccensis sample for more conformation. Raw 264.7 macrophage cells and HacaT cells were used, together with the MTT, ROS, NO, and wound healing assays, to investigate the possible cytotoxicity in A549 lung cancer. Thus, A. agallocha and A. malaccensis showed significant cytotoxicity against A549 cancer cells at 1000 µg/mL. Furthermore, we observed an elevated ROS level in cancer cells. The wound healing assay showed cancer cell inhibition activity. While BCL-2 decreased in the intrinsic route, p53, Bax, Caspase 3, and Caspase 9 were elevated by A.A and A.M. Additionally, we have also conducted an in silico evaluation followed by molecular dynamics (MD) simulations, along with ADMET and biological activity prediction to further validate the experimental results. In normal cells, both samples showed less toxicity at 1000 µg/mL and suppressed the LPS-treated NO and ROS levels against the inflammation. Additionally, A.A and A.M suppressed the pro-inflammatory gene expression of COX-2, iNOS, TNF-α, IL-6, and IL-8 in RAW 264.7 cells. On the other hand, A.A and A.M extract effectively suppressed oxidative stress by increasing the antioxidative gene expression in H2O2-induced HaCat cells at 50 μg/mL. This study revealed that the plant extracts from A. agallocha and A. malaccensis could exert a cytotoxic effect on lung adenocarcinoma cells through the activation of an intrinsic signaling pathway. Moreover, it could be a potential source of anti-inflammatory, antioxidant, and anti-cancer agents after consideration of in vivo and clinical studies.